Osseous Stress Injuries: Treatment Algorithms and Return to Play - Sax, Alessandra J. (Seminars in Musculoskeletal Radiology, 2024)
Osseous stress injuries are common in athletes. Specifically, lower extremity injuries are prevalent in running athletes and upper extremity injuries are prevalent in throwing athletes. Such injuries are suspected when there is focal bone tenderness and increased pain with the inciting activity. In elite athletes, osseous stress injuries are a relatively common culprit in lost play time. Thus rapid diagnosis and treatment is imperative to expedite return to play (RTP). The radiologist's role in these cases is not only for diagnosis, but also to grade the injury, which has implications in determining a treatment regimen. The high sensitivity and specificity of magnetic resonance imaging is thus the preferred imaging modality. This article discusses common osseous stress injuries, the imaging findings, and how different treatment regimens affect RTP.
Keywords: osseous stress; overuse injuries; return to play; return to sport